OPTIMALISASI TEKNOLOGI PENDIDIKAN DALAM MENDUKUNG PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - sembiring, Eliezer; Tumanggor, Nasrun; Pohan, Trinanda Putra; Peranginangin, Riwan Jordan; Hutagalung, Trisnawati (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to examine the role of digital technology in improving the quality of Indonesian language learning in elementary schools. The background of this research is the limited use of technology and the dominance of conventional teaching methods, which often result in low student engagement and learning effectiveness. This study employed a qualitative approach using a literature review method by analyzing relevant national and international journal articles published in the last ten years. Data were collected through systematic searches using academic databases such as Google Scholar and were analyzed using content analysis techniques. The results of the study indicate that the integration of digital technology, such as interactive learning media, educational videos, online learning platforms, and digital assessment tools, can significantly enhance students’ motivation, participation, and comprehension in Indonesian language learning. Technology also supports the development of students’ language skills, including reading, writing, speaking, and listening, through more engaging and contextual learning experiences. However, challenges remain, including limited technological infrastructure, unequal access to digital resources, and insufficient teacher competence in utilizing technology effectively. Therefore, continuous teacher training, adequate infrastructure support, and policy alignment are essential to optimize the use of technology in Indonesian language learning at the elementary school level.